Crystal structure of rac-1,8-bis(2-carbamoylethyl)-5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane, C22H46N6O2 - Paul Pradip; Yasmin Sabina; Rabi Saswata; Rahman Ismail M. M.; Tiekink Edward R. T.; Roy Tapashi Ghosh (Zeitschrift für Kristallographie - New Crystal Structures)
C22H46N6O2, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 8.5777(3) Å, b = 9.0205(4) Å, c = 9.9270(3) Å, α = 67.899(3)° $67.899(3){}^{°}$ , β = 71.106(3)° $71.106(3){}^{°}$ , γ = 63.774(4)° $63.774(4){}^{°}$ , V = 626.83(5) Å3, Z = 1, Rgt ${R}_{gt}$ (F) = 0.0400, wRref $wR_{ref}$ (F 2) = 0.1162, T = 298(2) K.